Physical capacity and functional resources of the respiratory system of young footballers with various biological development - Петренко [Sergiy Petrenko], Сергій Іванович (Slobozhanskyi Herald of Science and Sport, 2013)
The aim of the work was to determine the physical capacity and function of the respiratory system of young footballers with various biological development. The study involved 84 young footballers aged 12–14 years, who trained four times a week on the program Youth Academy. All adolescents were divided into three groups according to their level of biological development. Players were identified with decelerated, normal and accelerated biological development. There were that indicators of capacity (on the test PWC170), and functional parameters of the respiratory system (number of breaths per minute, retardation the breath to inhale and exhale, and maximum consumption oxygen) of grew as growing young athletes. At the same time, within the same age period of one young rated age did not show similar estimated parameters. The best indicators were in adolescents with accelerated biological development, and the worst – with decelerated. So, it was shown that rated age may be different from the biological. The conclusions about the need to consider the biological development of adolescents in the process of selecting to football sections, and in the planning exercise, which must be individually metered to prevent overtraining.